Good Corporate Governance terhadap Biaya Ekuitas dan Biaya Hutang - Dista Amalia Arifah; Vita Eva Liana (Jurnal Bisnis dan Ekonomi, 2018)
The purpose of this research was to determined the impact of good corporate governance on cost of equity and cost of debt. Corporate governance perception index (CGPI), family ownership, institutional ownership, and independent commissioner as Corporate Governance proxied. Population in this research was The Indonesian Stock Exchange (BEI) listed companies and joined The Indonesian Institute for Corporate Governance (IICG) in 2011-2013. Purposive sampling was used as sampling technique and obtained 63 samples of the company. Multiple linear regression was used as technical analysis. The result showed that Corporate Governance perception index and independent commissionerdid not affect significantly on cost of equity. While family ownership and institutional ownership had negatively significant with cost of equity. Other result noted that corporate governance perception index, family ownership, institutional ownership and independent commissionerdid not significantly with cost of debt